2020
DOI: 10.1063/5.0008665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium oxide adhesion layer on resonance behavior of plasmonic nanostructures

Abstract: The magnesium oxide (MgO) adhesion layer is proposed to avoid adverse effects of lossy metallic adhesion layers in thin film plasmonic nanostructures. Such adverse effects can be in the form of resonance broadening and a decrease in the resonance magnitude. We fabricate and test the quality of MgO adhesion layers and determine its optical properties through ellipsometry measurements. We also provide the plasmonic response of various plasmonic nanostructures (nanohole array, nanodisk array, dimer nanohole array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As a result, the performance of the SPR decreases (Ekgasit et al, 2005;Jeppesen et al, 2010;Najiminaini et al, 2011;Otte et al, 2011;Hughes et al, 2012;Abbott et al, 2019). Some studies have proposed using oxides such as ITO, TiO 2 , and Cr 2 O 3 as adhesion layers to reduce losses (Aouani et al, 2009;Djaker et al, 2010;Sadri-Moshkenani et al, 2020). These oxides are low-loss materials at optical wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the performance of the SPR decreases (Ekgasit et al, 2005;Jeppesen et al, 2010;Najiminaini et al, 2011;Otte et al, 2011;Hughes et al, 2012;Abbott et al, 2019). Some studies have proposed using oxides such as ITO, TiO 2 , and Cr 2 O 3 as adhesion layers to reduce losses (Aouani et al, 2009;Djaker et al, 2010;Sadri-Moshkenani et al, 2020). These oxides are low-loss materials at optical wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…These oxides are low-loss materials at optical wavelengths. In a recent work (Sadri-Moshkenani et al, 2020), it has been demonstrated that low-loss magnesium oxide (MgO) could be the best alternative for the conventional adhesion layers and other adhesion layers proposed in the earlier works. Hence, in this work, MgO is chosen as the adhesive layer of the proposed structure of the SPR sensor.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the low optical conductivity 525 of permalloy 367,526 and thus, high damping factors for any type of plasmonic resonance. In addition, silicon as substrate material exhibits a high refractive index that significantly red-shifts, damps and broadens electromagnetic resonances 371,527 . Nevertheless, indications for plasmonic resonances have been found during optical damagethreshold tests using laser pulses.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…This may be due to the low optical conductivity [50] of permalloy [51,52] and thus, high damping factors for any type of plasmonic resonance. In addition, silicon as substrate material exhibits a high refractive index that significantly red-shifts, damps and broadens electromagnetic resonances [53,54]. Nevertheless, indications for plasmonic resonances have been found during optical damage-threshold tests using laser pulses.…”
Section: Summary and Perspectivementioning
confidence: 99%